Progress in diagnosis and treatment of functional tremor - Wan⁃lin LI; Yuan GAO; Qin⁃ying MA; Yan DING; Shu⁃juan TIAN; Hua⁃long WANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2023)
Functional tremor (FT) is the most common manifestation of functional movement disorder (FMD), but its clinical recognition is insufficient, and there is no clear diagnostic standard and effective treatment method at present. The diagnosis mainly depends on the medical history, clinical examination, physical signs, neuroelectrophysiological examinations. Early diagnosis and treatment are essential to improve the prognosis of the patients. The etiology and pathogenesis of FT have not been clarified. This article reviews the progress in diagnosis and treatment of FT in order to improve the clinicians' understanding of the disease and provide the possibility for treatment.